2016
DOI: 10.1021/jacs.6b00849
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks Stabilize Solution-Inaccessible Cobalt Catalysts for Highly Efficient Broad-Scope Organic Transformations

Abstract: New and active earth-abundant metal catalysts are critically needed to replace precious metal-based catalysts for sustainable production of commodity and fine chemicals. We report here the design of highly robust, active, and reusable cobalt-bipyridine- and cobalt-phenanthroline-based metal-organic framework (MOF) catalysts for alkene hydrogenation and hydroboration, aldehyde/ketone hydroboration, and arene C-H borylation. In alkene hydrogenation, the MOF catalysts tolerated a variety of functional groups and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
145
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 223 publications
(148 citation statements)
references
References 58 publications
2
145
0
1
Order By: Relevance
“…The very-weak-field coordination environment consisting of O-atoms that the UiO-M (M=Co, Fe) framework provides is very different than those accessible to molecular catalysts that typically consist of stronger field N- or P-donor atoms. Indeed, bipyridine and phenathroline-based MOF-Co catalysts were recently reported to be active in borylation of arene C–H bonds instead of benzylic C–H bonds52. Beyond the low coordination number, weak-field catalyst sites that lead to high electrophilicity are possible in these MOFs but are simply not available to small molecule homogeneous catalyst systems because ligands based on weakly binding O-donors would readily dissociate from first row transition metals.…”
Section: Discussionmentioning
confidence: 99%
“…The very-weak-field coordination environment consisting of O-atoms that the UiO-M (M=Co, Fe) framework provides is very different than those accessible to molecular catalysts that typically consist of stronger field N- or P-donor atoms. Indeed, bipyridine and phenathroline-based MOF-Co catalysts were recently reported to be active in borylation of arene C–H bonds instead of benzylic C–H bonds52. Beyond the low coordination number, weak-field catalyst sites that lead to high electrophilicity are possible in these MOFs but are simply not available to small molecule homogeneous catalyst systems because ligands based on weakly binding O-donors would readily dissociate from first row transition metals.…”
Section: Discussionmentioning
confidence: 99%
“…Postsynthetic modication (PSM) in general, [53][54][55] and speci-cally metalation of chemically stable MOFs containing free bipy sites, [56][57][58][59][60][61][62] have proven to be highly efficient methods to enhance the properties of MOFs, and so we attempted metallation of 2-HCl with CuCl 2 as a proof-of-concept transformation with the aim of introducing group 10 metals for catalytic applications, as well as potentially adding suitable steric bulk to stop the material adopting a closed pore form on drying (see ESI, Section S9 †). Single crystals of 2-HCl were metallated by immersion in an anhydrous DMF solution containing CuCl 2 at 60 C for 42 hours.…”
Section: Metallation Ofmentioning
confidence: 99%
“…We recently showed that highly active basemetal catalysts can be stabilized in bipyridyl-based MOFs via active site isolation, while analogous homogeneous catalysts undergo rapid intermolecular deactivation via ligand disproportionation reactions. 20 Herein, we report a simple strategy to stabilize active heteroleptic Mg-alkyl species at secondary building unit (SBUs) of TPHN-MOF (TPHN = 4,4′-bis-(carboxyphenyl)-2-nitro-1,1′-biphenyl) to afford highly active and reusable single-site solid catalysts for hydroboration of carbonyl and imine compounds and for hydroamination of aminoalkenes. Site isolation within the MOF stabilizes catalytically active heteroleptic Mg-alkyl species by shutting down Schlenk-type intermolecular ligand redistribution reactions ( Figure 1).…”
mentioning
confidence: 99%